TERRAIN TECTONICS OF THE CENTRAL ASIAN FOLDED BELT - M. M. Buslov (Геодинамика и тектонофизика)
The terrain analysis concept envisages primarily a possibility of approximation of fragments / terrains of various geodynamic settings which belong to different plates. The terrain analysis can supplement the theory of plate tectonics in solving problems of geodynamics and tectonics of regions of the crust with complex structures. The Central Asian belt is among such complicated regions. Terrain structures occurred as a result of combined movements in the system of 'frontal' and/or oblique subduction – collision. In studies of geological objects, it is required first of all to prove their (vertical and horizontal) autochthony in relations to each other and then proceed to paleogeodynamic, paleotectonic and paleogeographic reconstructions. Obviously, such a complex approach needs data to be obtained by a variety of research methods, including those applied to study geologic structures, stratigraphy, paleontology, paleogeography, lithothlogy, geochemistry, geochronology, paleomagnetism etc. Only by correlating such data collected from inter-disciplinary studies of the regions, it is possible to establish reliable characteristics of the geological settings and avoid mistakes and misinterpretations that may be associated with the 'stratigraphic' approach to solutions of both regional and global problems of geodynamics and tectonics of folded areas. The terrain analysis of the Central Asian folded belt suggests that its tectonic structure combines marginal continental rock complexes that were formed by the evolution of two major oceanic plates. One of them is the plate of the Paleo-Asian Ocean. As the analogue of the current Indo-Atlantic segment of Earth, it is characterised by the presence of continental blocks in the composition of the oceanic crust and the formation of oceanic basins resulting from the breakup of Rodinia and Gondvana. In the course of its evolution, super-continents disintegrated, and the blocks were reunited into the Kazakhstan-Baikal continent. The base of the Kazakhstan-Baikal continent was formed in the Vend-Cambrian due to subduction of the oceanic crust of the Paleo-Asian Ocean, including the Precambrian microcontinents and terrains of the Gondvana group, underneath the south-eastern margin of the Siberian continent (in the current coordinates). Due to subduction followed by collision of the microcontinents with the Kazakhstan-Tuva-Mongolia island arc, the crust had consolidated, and a complex continent was formed. Another major plate is the plate of the Paleo-Pacific Ocean. It is characterized by the long-term tectono-magmatic evolution without any involvement of the continental crust and by complex processes of the formation of the continental margins. Its evolution resulted in the formation of the Vend-Paleozoic continental margin complexes of the western segment of the Siberian continent which comprise the Vend-Cambrian Kuznetsk-Altai island arc and a complex of rocks of the Ordovic-Early Devonian passive margin and the Devon-Early Carbonic active margin. In the accretional wedges of the Kuznetsk-Altai island arc, abundant are only fragments of the Vend-Early Cambrian oceanic crust including ophiolites and paleo-oceanic uplifts. The contemporary analogue of the Central Asian folded belt is the south-eastern margin of Asia, represented by the junction area of the Indo-Australian and Pacific plates.